DAMPAK IMPLEMENTASI FORMULA UPAH MINIMUM SESUAI PERATURAN PEMERINTAH NOMOR 78 TAHUN 2015 TENTANG PENGUPAHAN TERHADAP KESEJAHTERAAN PEKERJA DI KABUPATEN BEKASI. - Timbul Handriyanto; Mahayoni Mahayoni (Problematika Hukum, 2018)
The Constitution states that every citizen has the right to work and a decent living for humanity, reinforced by the Manpower Act that every worker/laborer has the right to earn an income that fulfills a decent living for humanity. In achieving this goal, the state establishes a "Minimum Wage" based on a survey of the basic needs of a single worker for one month called the Decent Living Needs (KHL). The Government issued Government Regulation 78 of 2015 concerning Wages which regulates the formula for setting minimum wages based on inflation and national economic growth, the components of the decent living necessities that were previously used as a basis for stipulations are no longer used. This type of research is normative juridical legal research, using the IRAC analysis approach (issue, rule, analysis, conclusion) to draw a conclusion. Data and data sources used are primary data and secondary data with the procedure of collecting literature and field studies. From the results of the study the Impact of the Implementation of the Minimum Wage Formula in Accordance with Government Regulation Number 78 Year 2015 Regarding Wages Against Workers' Welfare is the average increase in wages in Bekasi district, five years before and after the formula was put in place experienced a significant decrease. The minimum wage, which was five years earlier above the KHL, is now below the KHL. The formula also makes wage increases as a percentage flat, resulting in wider regional wage disparities. The problems studied are: 1. The mechanism for setting minimum wages before and after the birth of PP 78 of 2015 concerning wages. 2. The impact of the implementation of the minimum wage formula in accordance with PP 78 of 2015 concerning wages for workers' welfare. Keywords: Minimum Wages, PP 78/2015 Formula, and Living Needs (KHL).